1992
DOI: 10.1159/000276302
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Structure and Function in a Recessive Type of Genetically Induced Inner Ear Degeneration

Abstract: An age-related consecutive morphological analysis of the cochlea has been performed in homozygote (Je/Je) and heterozygote (je/+) jerker mouse mutants. A difference in the time of onset of hair cell pathology was evident between the two, but, when taking place, it showed a similar morphological type of degeneration. The cuticular plate and the stereocilia are particularly vulnerable structures and are the primary sites of damage. The suprastructures on both outer and inner hair cells disintegrate at the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
0
23
2
Order By: Relevance
“…Inner ear dysfunction in spinner mice results from mutations in Tmie, which encodes a novel protein with predicted transmembrane domains . Jerker mice, deficient in the actin bundling protein espin, exhibit a variety of hair cell defects, including shortened stereocilia by P12 [Sjostrom and Anniko, 1992a, b]. Hair cells of shaker 2 mice, which lack normal Myo15 function, also possess extremely short stereocilia bundles Probst et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Inner ear dysfunction in spinner mice results from mutations in Tmie, which encodes a novel protein with predicted transmembrane domains . Jerker mice, deficient in the actin bundling protein espin, exhibit a variety of hair cell defects, including shortened stereocilia by P12 [Sjostrom and Anniko, 1992a, b]. Hair cells of shaker 2 mice, which lack normal Myo15 function, also possess extremely short stereocilia bundles Probst et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of hearing physiology showed that jerker mice were totally deaf from the first time point such measurements could be carried out [30,31]. Electron microscopic studies in the early 1990's revealed a pronounced shortening and degeneration of stereocilia in the cochlear hair cells of jerker mice, defects that became pronounced near the onset of hearing around postnatal day 10 [32,33]. Occasional defects, such as protrusion and folding of the cuticular plate, were also noted in the cochlear hair cells of newborn jerker mice.…”
Section: Jerker Deafness Mutation In the Mouse Espin Genementioning
confidence: 99%
“…Phenotypically, mice that are hetereozygous for the jerker mutation (jerker heterozygotes) appear relatively normal. Although aged jerker heterozygotes have been reported to show stereociliary and hair cell degeneration [32,33], it is presently unclear whether these defects are related to the jerker mutation or are associated with age-related hearing loss, which is evident in a number of inbred mouse strains [36]. Unfortunately, the reports of cochlear defects in aged jerker heterozygotes [32,33] used mice of a different background strain (CBA) as wild-type controls, and to our knowledge wild-type mice of the standard inbred jerker mouse strain (JE/LeJ, stock number 000249) obtained from the Jackson Laboratory (Bar Harbor, Maine, USA) have not yet been tested for age-related hearing loss.…”
Section: Jerker Deafness Mutation In the Mouse Espin Genementioning
confidence: 99%
See 1 more Smart Citation
“…There is no topographical gradient in the progression of cochlear duct pathology, which means that all parts of the cochlea become affected simultaneously. The specific degenerative changes are followed by less specific changes including shrinkage, vacuolization and ultimately total disintegration of the hair cells [7], Vestib ular hair cells are similarly affected [8], Only a few effer ent nerve endings were seen at the base of the cochlear hair cells.…”
Section: Introductionmentioning
confidence: 99%